1997
DOI: 10.1128/jcm.35.12.3186-3191.1997
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the BBL Crystal Anaerobe identification system

Abstract: The BBL Crystal Anaerobe (ANR) identification system was evaluated, and the results were compared with those from conventional anaerobic methods. We tested 322 clinically significant anaerobic bacteria according to the manufacturer's instructions. The system identified correctly 286 of 322 (88.8%) of the anaerobic bacteria tested. Of these, 263 of 322 (81.7%) were identified correctly on initial testing and 49 were identified correctly only to the genus level; on repeat testing, 23 of 49 (46.9%) were identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…For final identification, it was necessary to perform additional tests (production of acid from arabinose, trehalose, and xylane) to discriminate between B. fragilis, B. thetaiotaomicron, B. ovatus, and B. uniformis. It has been reported that misidentification of most Bacteroides species often involves B. thetaiotaomicron (2,3). For such isolates, up to 48 h can be required for further identification assays.…”
Section: Development Of Pcrmentioning
confidence: 99%
See 1 more Smart Citation
“…For final identification, it was necessary to perform additional tests (production of acid from arabinose, trehalose, and xylane) to discriminate between B. fragilis, B. thetaiotaomicron, B. ovatus, and B. uniformis. It has been reported that misidentification of most Bacteroides species often involves B. thetaiotaomicron (2,3). For such isolates, up to 48 h can be required for further identification assays.…”
Section: Development Of Pcrmentioning
confidence: 99%
“…Species identification often requires 3 to 7 days and sometimes is inconclusive (19). The automated methods currently used are sometimes unreliable at identifying B. thetaiotaomicron clinical isolates or other species (2,3). The phenotypic and biochemical similarity of closely related species makes it difficult to discriminate them.…”
mentioning
confidence: 99%
“…These are time‐consuming, and it may be difficult to differentiate Bacteroides species with them [8,9]. Automated methods currently used are also unreliable for identifying isolates of the B. fragilis group [10,11]. Incorrect identification of strains of the B. fragilis group may result in inappropriate antibiotic therapy.…”
Section: Introductionmentioning
confidence: 99%